High density lipoprotein is an inappropiate substrate for hepatic lipase in postmenopausal women - Zago, Valeria (2012)
Background HDL antiatherogenic effects would not only depend on its concentration but also on its biological quality. Hepatic lipase (HL) action on HDL acts in one of the last steps of reverse cholesterol transport. Cardiovascular risk increases after menopause, however HDL does not decrease even when HL is increased. We evaluated HDL capacity as a substrate of HL in healthy postmenopausal women (PMW). Methods We studied 20 PMW (51–60 y) and 20 premenopausal (PreMW) (26–40 y). In fasting serum, lipid–lipoprotein profile and HDL composition were assessed. Optimal assay conditions for HDL/HL ex vivo incubation were established. Increasing HDL–triglyceride concentrations (0.015 to 0.20 mmol/l) were incubated with post-heparin plasma obtained from a single healthy donor as a source of HL. Free fatty acids were measured and kinetic parameters calculated: Km(app), inverse to enzyme affinity, and Vmax. Results HDL composition in PMW exhibits triglyceride enrichment (p < 0.001). Kinetic analysis revealed higher Km(app) in PMW [130 (40–380) vs 45 (20–91) mmol/l, p < 0.0001)] correlating directly with HDL–triglycerides (r = 0.7, p = 0.0001). Catalytic efficiency, Vmax/Km(app) was reduced when compared to controls (p = 0.0001). Conclusion Triglyceride-enriched HDL from PMW constitutes a poor substrate for HL suggesting that this particle may not exert efficiently its antiatherogenic function, regardless of plasma concentration.